2010
DOI: 10.17221/19/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preventive application of Enterococcus faecium EF55 on intestinal mucosa during salmonellosis in chickens

Abstract: In the present study the effect of preventive application of <I>Enterococcus faecium</I> EF 55 on the intestinal mucosa was evaluated in experimentally infected chickens with <I>Salmonella enterica</I> subsp. <I>Enteritidis</I>. A total of 120, one-day-old <I>Salmonella</I>-free chickens of Isa Brown hybrid were divided into 4 groups. The chickens in groups E and ES were perorally inoculated with <I>E. faecium</I> EF55 in a dose of 1 × 109 CFU/ml for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Interestingly, the inflammatory process starts to be downregulated at 4 D after SE infection when anti-inflammatory cytokines (IL-10, tumor necrosis factor-ß) and the number and function of regulatory T cells are upregulated (Shanmugasundaram et al, 2015; Kogut et al, 2016). Because of the resulting SE tolerance, the pathogens often persist in the host's intestinal tract (particularly in the caeca) without visible clinical signs (Herich et al, 2010). Carrier birds excrete the bacteria intermittently and constitute an important source of infection (Ducatelle et al, 2000; Kogut et al, 2016; Velasquez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the inflammatory process starts to be downregulated at 4 D after SE infection when anti-inflammatory cytokines (IL-10, tumor necrosis factor-ß) and the number and function of regulatory T cells are upregulated (Shanmugasundaram et al, 2015; Kogut et al, 2016). Because of the resulting SE tolerance, the pathogens often persist in the host's intestinal tract (particularly in the caeca) without visible clinical signs (Herich et al, 2010). Carrier birds excrete the bacteria intermittently and constitute an important source of infection (Ducatelle et al, 2000; Kogut et al, 2016; Velasquez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Carrier birds excrete the bacteria intermittently and constitute an important source of infection (Ducatelle et al, 2000; Kogut et al, 2016; Velasquez et al, 2018). Salmonellae also colonize the Peyer's patches, from which they can disseminate into the liver and spleen (Monack et al, 2000; Crhanova et al, 2011); these organs are the sites of intracellular proliferation and the spreading of the bacteria causing systemic diseases with the translocation and dissemination of toxins and bacteria to various internal organs (Vasquez-Torres et al, 1999; Levkut et al, 2009; Herich et al, 2010; Iheukwumere et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the probiotics used today belong to the Lactobacillus group (Jenkins et al, 2005). New probiotic strains with antimicrobial effects can be isolated from plants and animals (Marciňáková et al, 2008;Herich et al, 2010).…”
mentioning
confidence: 99%
“…The majority of the probiotics used today belong to the Lactobacillus group (Jenkins et al 2005). New probiotic strains with antimicrobial effects can be isolated from plants and animals (Marciňáková et al 2008;Herich et al 2010). Some studies showed that a high fat diet increased the risk of colon cancer (Meyerhardt et al 2007).…”
mentioning
confidence: 99%